Amalan Komunikasi Di Kalangan Pentadbir Pendidikan Di Daerah Kuala Muda - Noriza, Mohamed Nasir (2001)

(untitled)
The purpose of this study is to identify the factors that influence the effectiveness of communication in secondary schools in Kuala Muda District, Kedah Darul Aman. The selected factors are gender, age, experience, media used and leadership style. A total of 107 sets of questionnaires were distributed to the respondents, who are the education administrators in daily secondary schools in Kuala Muda District, Kedah Darul Aman. Out of that, 101 sets were answered and returned. The data obtained were analyzed using descriptive statistic and Pearson Correlation Coefficient. The result of the study showed that the education administrators in this district often use interpersonal communication such as meeting and talking personally to the individual involved. Meanwhile, majority of them said that they had never used the electronic mail to send messages to the staff in schools. The study also showed that there was no significant relationship between communication effectiveness and gender, age, experience or media used. On the other hand, there was a significant relationship between communication effectiveness and leadership style.